Model Pengembangan Zakat Produktif Studi Komparatif di Indonesia dan Brunei Darussalam - Saputra, Andrian (Fakultas Syariah IAIN Kediri, 2024)
This research examines the productive zakat development model in Indonesia and Brunei Darussalam through a comparative approach. Productive zakat is an effort to utilize zakat funds to improve the economic welfare of mustahik in a sustainable manner. In Indonesia, zakat is regulated by Law no. 23 of 2011 and managed by the National Amil Zakat Agency (BAZNAS) and various Amil Zakat Institutions (LAZ). Meanwhile, in Brunei Darussalam, zakat is managed by the Brunei Islamic Religious Council (MUIB) based on sharia law. This study found that the two countries have different approaches but both focus on empowering the mustahik economy through programs such as providing business capital, skills training and assistance with production equipment. Indonesia shows diversity in program implementation with extensive collaboration between various institutions, while Brunei Darussalam utilizes full government support for more focused and effective program implementation. Challenges facing Indonesia include unequal distribution and weak supervision, while Brunei faces challenges in economic diversification. However, both countries have great opportunities to increase the effectiveness of productive zakat programs through technological innovation and closer collaboration between the public and private sectors. This study provides insight into best practices and lessons that can be drawn from each country to improve the welfare of mustahik in a sustainable manner. The conclusion of this research emphasizes the importance of strengthening the legal and institutional framework, as well as increasing transparency and accountability in the management of productive zakat.